Análisis socio-económico de las mujeres usuarias de la Unidad Judicial Tercera de Violencia contra la mujer y la familia del cantón Quito-parroquia de Carapungo - Canelos Escalante, Mariela Karina (2015)
The domestic violence is the violation of rights of the all members, such us: freedom of conscience, freedom of has a decent life, freedom of have a good heath, psychology, sexual, furthermore the attack can be realized to any member of the family. That’s the reason why our propose is labor insertion for all the victims, according to the last research, lost of victims depends on aggressor economically. In order to stop it, and they will have a good and decent life, we´re searching the best way to introduce them in the labor. All of the victims need to work, and have their money in order to supply of the necessities. With the project, the attacks will stop, and all of the problems that it causes too. Like depressive, frustration, all of the things that affects the family neclo, especially to de siblings. Because it will produce negative effects in their life’s.